Investigating the Construction of Ijma in The Study of Islamic Law through Sociological and Historical Approach - Tri Hidayati; Muhammad Syarif Hidayatullah (Sharia and Law Faculty, 2021)
This paper aims to examine the construction of ijma in the study of Islamic law through sociological and historical approaches. The research looks at qualitative data through literature studies. In legal research methods, this research is categorized as normative legal research with a conceptual approach. The concept of ijma becomes the object of study in this paper. Furthermore, the concept of ijma is examined with socio-historical analysis. The results of the discussion show that the difference in views on the concept of ijma as the basis of Islamic law that must be obeyed, influenced by normative arguments (propositions of the Qur'an and sunnah) which are references and different interpretations of legal propositions held as a basis of opinion. The difference in looking at the concept of ijma that can be used as a Islamic legal argument also begins from the difference in setting the standard of definition and criteria (pillars and conditions) of the ijma itself and considering the capacity of the ijma whether as an opinion of